Fostering Clean and Healthy Energy in Rural Communities: Lessons from the Indonesia Clean Stove Initiative Pilot Program - Widijantoro, Johanes; Windarti, Yuni (International Journal of Energy Economics and Policy, 2018)
Most of rural people still use traditional wood-fired stoves in their daily life but it was classified as unclean, unhealthy, and inefficient. Indoor air pollution caused by the burning of solid fuels in traditional stoves is one of the leading risk factors attributed to mortality and burden of disease. This paper is aimed to reveal efforts to promote using of clean cook stove among households in rural areas. Based on technological touch followed by laboratory tests, clean stoves are claimed have its efficiency in fuel use and its capacity on reducing negative impact levels for its users such as suppress levels of carbon dioxide, fine dust, and smoke. By having the CSI pilot program, it is expected that lessons learned from the pilot program would create sustainable market for clean cook stoves in Indonesia because most consumers respond positively to the presence of a clean, healthy and energy-efficient stoves. Keywords: clean energy, clean stove, consumer. JEL Classification: Q280 DOI: https://doi.org/10.32479/ijeep.7085